Database design with common sense business reasoning and learning. - Storey, Veda C.; Chiang, Roger H. L.; Dey, Debabrata; Goldstein, Robert C.; Sudaresan, Shankar
Automated database design systems embody knowledge about the database design process. However, their lack of knowledge about the domains for which databases are being developed significantly limits their usefulness. A methodology for acquiring and using general world knowledge about business for database design has been developed and implemented in a system called the Common Sense Business Reasoner, which acquires facts about application domains and organizes them into a a hierarchical, context-dependent knowledge base. This knowledge is used to make intelligent suggestions to a user about the entities, attributes, and relationships to include in a database design. A distance function approach is employed for integrating specific facts, obtained from individual design sessions, into the knowledge base (learning) and for applying the knowledge to subsequent design problems (reasoning).
Keywords: Common sense business reasoner; Common sense learning; Common sense reasoning; Database design; Entry-relationship model